Animasi Gambar dengan Menggunakan Avatar Editor dan 3dMax - Sri Siswanti, Andriani Kusumaningrum (Jurnal Ilmiah SINUS, 2010)
Animation, or more familiarly known as the animated film, is a film that is the result of image processing so that the hand into a moving image. In making this aniamsi using images from the front and sides as well as video recordings. Photo edited using the avatar editor, is a video on the analysis using facelifter. Merging photos with videos that have been edited using 3DMax software. The results of this animation is the appropriate model to be photographed doing the movement and sound in accordance with the recorded video. keywords : animation, facelifter